1952
DOI: 10.1021/ja01136a053
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Dilute Solutions of Magnesium Halides in Ethanol at 20° from Conductance Measurements1,2

Abstract: for all cases, but generally becomes smaller for a faster reaction and smaller diffusion coefficient. However, values of µ from 10~1 2 to 10~3 45cm. will at least predict the order of magnitude of the rate constants for the cases where the re-action involves a reduction product of the electrode, and values closer to 10~7 cm. for reactions that precede the electrode reduction. Chicago, Illinois

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

1958
1958
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
5
1
Order By: Relevance
“…Studies of the ion association for a series of magnesium halides in ethanol have been made and very definitely support the concept that the association of the C1-ion with the Mg+2 ion is greater than are similar associations involving the Br-and I-ions. 23 In the solvent system which is employed for the casting solutions from which semipermeable membranes of cellulose acetate are cast, acetone predominates over water. The dielectric constant of the acetone-water medium is substantially lower than that of pure water, and the possibility of ion associations is consequently greatly enhanced.…”
Section: Swelling Of Secondary Celldose Acetatementioning
confidence: 99%
“…Studies of the ion association for a series of magnesium halides in ethanol have been made and very definitely support the concept that the association of the C1-ion with the Mg+2 ion is greater than are similar associations involving the Br-and I-ions. 23 In the solvent system which is employed for the casting solutions from which semipermeable membranes of cellulose acetate are cast, acetone predominates over water. The dielectric constant of the acetone-water medium is substantially lower than that of pure water, and the possibility of ion associations is consequently greatly enhanced.…”
Section: Swelling Of Secondary Celldose Acetatementioning
confidence: 99%
“…Pertinent chemical properties of MEA have been reviewed (4). On the assumption that metal contaminants, particularly iron, catalyzed oxidative breakdown of MEA, a chelating agent, the monosodium salt of NjlV-diethanolglycine (2) (VFS), is now a required constituent of base stock MEA procured for submarine scrubber use (3).…”
Section: Resultsmentioning
confidence: 99%
“…For MgCl2, MgBr2, and Mgl2 dissolved separately in ethyl alcohol, Dawson and Golben (2) reported that the firststage ionization is essentially complete. As the Kohlrausch plots did not yield straight lines, they suggested that the Debye-Hiickel-Onsager equation was sensitive to valence changes.…”
mentioning
confidence: 99%
“…The possibility of using the Beilstein effect (12) to determine the halides has also been investigated (13,14). This method involves the use of a arrangement similar to that mentioned above except the indium coated surface is replaced with copper.…”
Section: Discussionmentioning
confidence: 99%